2017
DOI: 10.13189/aeb.2017.051105
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Motives and Challenges of SMEs Owners in Emerging Economies: Nigeria & South Africa

Abstract: This paper is a comparative analysis of the peculiarities of entrepreneurial motives and challenges that exist in emerging economies. The paper also emphasizes the fact that knowing what entrepreneurs are up against would get them prepared and inexorably minimize the effects of the challenges. Research findings show that entrepreneurs set up business ventures basically for various reasons, and individuals become entrepreneurs primarily due to pull, than push factors. 1200 samples were purposively drawn from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In a further outlook of the employment patterns, Figure 3 reveals the increased rate of selfemployment as against paid employees in Nigeria. Though these self-employments may not necessarily indicate high-level skills, it nonetheless shows the ease of small and medium business start-ups in Nigeria (Akinyemi and Adejumo, 2017) relative to finding paid or whitecollar jobs. Also, Figure 4 gives an insight into the pattern of sectoral distribution of employment in Nigeria.…”
Section: An Overview Of Education Policy In Nigeria: Implications For Employment Statusmentioning
confidence: 98%
“…In a further outlook of the employment patterns, Figure 3 reveals the increased rate of selfemployment as against paid employees in Nigeria. Though these self-employments may not necessarily indicate high-level skills, it nonetheless shows the ease of small and medium business start-ups in Nigeria (Akinyemi and Adejumo, 2017) relative to finding paid or whitecollar jobs. Also, Figure 4 gives an insight into the pattern of sectoral distribution of employment in Nigeria.…”
Section: An Overview Of Education Policy In Nigeria: Implications For Employment Statusmentioning
confidence: 98%
“…According to [38], while economic survival is the primary motivation for Mexican business people, Canadian and American business people value intrinsic pleasures more than perceptions of success. The research by [39] revealed entrepreneurial obstacles that are common to all emerging economies, despite situational differences. Motivations are also linked to corporate resources, behaviors, and performance [40].…”
Section: Entrepreneurial Motives (Emts)mentioning
confidence: 99%
“…Therefore, consumers' cultural (anthropology) origins may influence their food choices [32]. South Africa is classified as an emerging country due to its large markets for goods and services, and entrepreneurs that can compete globally if given adequate support [33]. A transition in food consumption behaviour has led to an increased intake of processed foods high in carbohydrates [34].…”
Section: A Cultural Perspectivementioning
confidence: 99%